ASSOCIATION BETWEEN INTENSIVE CARE UNIT TRANSFER DELAY AND HOSPITAL MORTALITY - NAWADAT , Q; KHALID, MA; PARVEEN , A (Biological and Clinical Sciences Research Journal, 2023)
This study assessed the impact of ICU admission delay on hospital mortality using electronic Cardiac Arrest Risk Triage (eCART). An observational cohort study was conducted in the Intensive care unit of Shifa International Hospital from April 2022- April 2023. A total of 400 patients admitted to medical and surgical wards were included in the study. The eCART score was used to estimate the extent of critical illness using demographic data from the records, vital signs, and laboratory data. A duration of 6 hours was considered a cut-off for the delay as it is usually a critical threshold in critically ill patients. The patients in both groups varied slightly with respect to age (69 vs. 71 years); all the other factors did not vary significantly. However, in-hospital mortality was higher in the delayed admission group (33.3%) than in the non-delayed group (25%). The length of ward stay did not vary between groups (1.3 vs. 1.4 days), but the total length of hospital stay was 2 days longer in the delayed transfer group. Based on the results, A delay in ICU admission is significantly related to high in-hospital mortality and longer hospital stays.